Need for sustainable event management in the Indian context. Issue 5 (3rd July 2020) - Tiwari, Mohit; Tiwari, Tripti; Chaudhary, Seema; Marwah, Aparna; Bawa, Daljeet Singh
Abstract: The organization of events is highly resource hungry and demands which can lead to waste of natural and artificial resources. Event Management in the Indian context is a hub of opportunities but management of the same is far away from sustainability and therefore requiring responsible decision making for effective forecasting, association and execution of an event. Thus, the crux of this paper is to (i) sustainability in event management (ii) conceptual framework for event management. This study would help event management companies to adopt green initiatives for effective implementation in sustainability for event management.